2006
DOI: 10.1007/s10461-006-9150-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediational Analysis in HIV/AIDS Research: Estimating Multivariate Path Analytic Models in a Structural Equation Modeling Framework

Abstract: Mediational analyses have been recognized as useful in answering two broad questions that arise in HIV/AIDS research, those of theoretical model testing and of the effectiveness of multicomponent interventions. This article serves as a primer for those wishing to use mediation techniques in their own research, with a specific focus on mediation applied in the context of path analysis within a structural equation modeling (SEM) framework. Mediational analyses and the SEM framework are reviewed at a general leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 58 publications
(63 reference statements)
0
103
0
Order By: Relevance
“…Also, as hypothesized, subjective sexual arousal mediated the effects of alcohol on risk-taking; alcohol had no direct effects on risktaking. In keeping with recently published guidelines for mediational analyses in HIV/AIDS research (Bryan et al, 2007), we used structural equation modeling to evaluate our mediational hypotheses. This approach allowed us to simultaneously consider multiple mediatonal paths, ruling out paths dependent on genital arousal and bolstered confidence in the mediational effects observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, as hypothesized, subjective sexual arousal mediated the effects of alcohol on risk-taking; alcohol had no direct effects on risktaking. In keeping with recently published guidelines for mediational analyses in HIV/AIDS research (Bryan et al, 2007), we used structural equation modeling to evaluate our mediational hypotheses. This approach allowed us to simultaneously consider multiple mediatonal paths, ruling out paths dependent on genital arousal and bolstered confidence in the mediational effects observed.…”
Section: Discussionmentioning
confidence: 99%
“…As hypothesized, self-reported sexual arousal during the risktaking vignette significantly predicted unprotected sex likelihood, β = .47, p < .001, with estimated likelihood increasing as self-reported sexual arousal increased. In addition to direct effects, we tested the significance of indirect effects, as recommended by Bryan et al (2007). Results showed that alcohol condition had a significant indirect effect on likelihood of unprotected sex via subjective sexual arousal, β = .09, p < .05.…”
Section: Likelihood Of Unprotected Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the impact of national policies on the R&D capacity may be subject to change due to the PPA or fiscal incentives. In theory, we can take PPA with fiscal incentives as the mediator between P1 and T1 [5,[60][61][62][63][64][65][66]. Similarly, the theoretical model includes three mediators: R&D capacity (i.e., C1 → T1 → T3), site availability (i.e., E2 → E1 → C2), and the fundamental infrastructure (i.e., E1 → S2 → C2).…”
Section: The Establishment Of the Causality Model Of Barriers (Theorementioning
confidence: 99%
“…However, the theoretical model of this study contains the presence of multiple mediators (Me), which change the original relationship between the independent variables (IV) and the dependent variables (DV) from direct effect (IV → DV) into an mediating effect (IV → Me → DV) [5,61,65,66]. In the consideration of the characteristics of the SEM method, we used the co-variance among variables, simultaneously to estimate the model parameters, and to test the goodness-of-fit between the theoretical models and the observed data [54,55,60,[62][63][64]. Therefore, by considering all the reasons mentioned above, the SEM oriented path analysis was the more suitable choice of method for the study.…”
Section: The Validation Of Causality Between Obstacles and Model Goodmentioning
confidence: 99%